Monetary Policy and Real Exchange Rate Dynamics in Sticky-Price Models - Carlos Carvalho; Fernanda Nechio (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2014)
We study how real exchange rate dynamics are affected by monetary policy in dynamic, stochastic, general equilibrium, sticky-price models. Our analytical and quantitative results show that the source of interest rate persistence - policy inertia or persistent policy shocks - is key. When the monetary policy rule has a strong interest rate smoothing component, these models fail to generate high real exchange rate persistence in response to monetary shocks, as policy inertia hampers their ability to generate a hump-shaped response to such shocks. Moreover, in the presence of persistent monetary shocks, increasing policy inertia may decrease real exchange rate persistence.
Keywords: F3; F41; E0; 330; real exchange rates; monetary policy; interest rate smoothing; PPP puzzle; persis- tence